2020
DOI: 10.1007/s41783-020-00087-9
|View full text |Cite
|
Sign up to set email alerts
|

Materiality of Edible Film Packaging in Muscle Foods: A Worthwhile Conception

Abstract: Muscle foods are extremely extensive food products that are relished throughout the world. They are known for their exclusive nutritional content and bio-availability however, at the same time, they also provide apposite media for the growth of pathogenic and spoilage microorganisms. Packaging seems to be a substantial approach to overcome this problem, but most of the packaging involves the usage of non-biodegradable and non-renewable material like plastic, nylon, polyester, etc. The alarming situation caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 153 publications
0
22
0
Order By: Relevance
“…In recent years, multicomponent or composite edible film from natural origin has been materialized as an emerging concept to improve film parameters, for the ability to withstand mechanical stress and handling during the transport (Bhagath & Manjula, 2019; Bharti et al, 2020). These binary films are advantageous over single‐component film of being improved tensile strength (TS), elongation at break (Thakur et al., 2016), and excellent barrier properties (Tavassoli‐Kafrani, Shekarchizadeh, & Masoudpour‐Behabadi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multicomponent or composite edible film from natural origin has been materialized as an emerging concept to improve film parameters, for the ability to withstand mechanical stress and handling during the transport (Bhagath & Manjula, 2019; Bharti et al, 2020). These binary films are advantageous over single‐component film of being improved tensile strength (TS), elongation at break (Thakur et al., 2016), and excellent barrier properties (Tavassoli‐Kafrani, Shekarchizadeh, & Masoudpour‐Behabadi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The single polymer edible film can provide protection to food products; whereas, the films developed from a single starch component exhibit poor barrier and mechanical properties (Bharti, Pathak, Alam, Arya, Basak, et al, 2020; Thakur et al, 2019). These inferior properties can be alleviated by the synergistic effect of different polymers (Al‐Hassan & Norziah, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are a category of hydrophobic or amphiphilic molecules including: fatty acids, mono-, di-and triglycerides, animal and vegetable oils and fats, fat-soluble vitamins, sterols, phospholipids, lecithins, sphingolipids, natural resins, waxes [109]. They are important structural constituents, and fuel molecules providing the necessary energy for health promotion and supporting immunity (especially omega-3 fatty acids, conjugated linoleic acid), [110].…”
Section: Plant-derived Bioactive Compounds Promoting the Human Healthmentioning
confidence: 99%
“…Therefore, lipids could be used either as coatings applied directly to food to provide a moisture barrier, or in combination with polysaccharides or proteins to create packaging films and coatings with low Water Vapor Permeability (WVP) and acting as a good barrier against gases such as O 2 and CO 2 [117]. It has been also suggested that the incorporation of lipids into films/coatings can improve cohesiveness, flexibility, hydrophobicity, and the moisture barrier properties of packaging [109].…”
Section: Plant-derived Bioactive Compounds Promoting the Human Healthmentioning
confidence: 99%
See 1 more Smart Citation